One‐step, simultaneous triple endoscopic nasobiliary drainage for hilar biliary stricture. Issue 1 (3rd June 2012) - Kawakubo, Kazumichi; Isayama, Hiroyuki; Mizuno, Suguru; Hirano, Kenji; Yamamoto, Natsuyo; Takahara, Naminatsu; Miyabayashi, Koji; Mohri, Dai; Sasaki, Takashi; Kogure, Hirofumi; Sasahira, Naoki; Tada, Minoru; et al.
Abstract : The management of advanced hilar malignant and benign biliary strictures remains difficult regardless of the advances in endoscopic biliary stenting. Endoscopic nasobiliary drainage (ENBD) is suitable for the management, but the number of ENBD tubes is limited by the diameter of the accessory channel of the duodenoscope. In the present study, we demonstrated the feasibility and safety of one‐step simultaneous triple ENBD insertion to manage hilar biliary strictures. A therapeutic duodenoscope with a 4.2‐mm accessory channel was advanced into the duodenum. Three guidewires were advanced into three different intrahepatic bile ducts, none of which communicated with the others.Then, the three 5‐Fr ENBD tubes were simultaneously inserted alongguidewire, one at a time. Three patients with hilar biliary stricture who suffered from acute cholangitis due to stent occlusion were successfully managed by one‐step, simultaneous triple ENBD insertion.There were no procedure‐related complications. One‐step simultaneous triple ENBD is the most suitable drainage method for patients with advanced hilar biliary obstruction, especially in the setting of acute cholangitis due to occlusion of the previously placed stent.